Effective Strategies to Overcome Learning Difficulties in Simple Past Tense and Past Continuous Tense for Fifth-Grade Elementary Students - Permana, Sandy Despian; Oktania, Saiba; Ramadhani, Nadia Suci; Sinuhaji, Desmalia Febrina; Ramadani, Nanda (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
This research explores the challenges faced by fifth-grade elementary students in understanding Simple Past Tense and Past Continuous Tense, along with strategies to improve their learning. Applying a qualitative case study approach, the study identifies both internal factors such as cognitive development, motivation, and prior language knowledge and external influences like teaching methods, educational tools, and support from their environment. Drawing from expert theories on language acquisition and instructional techniques, various solutions are examined, including interactive teaching, contextual learning, and digital tools that reinforce grammar concepts. The findings highlight that engaging learning environments, scaffolding strategies, and multimedia integration significantly enhance students' comprehension of Past Tense structures. Collaboration among teachers, students, and parents plays a crucial role in overcoming these obstacles, ensuring more effective and meaningful grammar instruction